2009
DOI: 10.1536/ihj.50.279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phase II Cardiac Rehabilitation on Job Stress and Health-Related Quality of Life After Return to Work in Middle-Aged Patients With Acute Myocardial Infarction

Abstract: SummaryThe aim of the present study was to clarify the effects of phase II cardiac rehabilitation (CR) on job stress and health-related quality of life (HRQOL) after return to work in middle-aged patients with acute myocardial infarction (AMI). A total of 109 middle-aged outpatients (57 ± 7 years) who completed a phase I CR program after AMI were enrolled, 72 of whom participated in a phase II CR program for 5 months after hospital discharge (CR group) and 37 who discontinued the phase II CR program after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 22 publications
1
26
0
1
Order By: Relevance
“…Specifically, the results showed that the best predictors of a satisfying RTW after cardiac invasive procedures were: job satisfaction for the pre-illness work environment, depression and ambition, independently of sociodemographic factors, medical factors and a type of RTW (full or partial). The key role in the RTW process after an acute cardiac event played by non-medical factors has been also explored by earlier research [3][4][5]9,[15][16][17][18][19][20][21][22][23]. Recent studies have shown that the perception of work environment, which can be reflected in work stress and job satisfaction, has a strong effect on both people's decision to RTW [16,21,22] and duration of sickness absence [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, the results showed that the best predictors of a satisfying RTW after cardiac invasive procedures were: job satisfaction for the pre-illness work environment, depression and ambition, independently of sociodemographic factors, medical factors and a type of RTW (full or partial). The key role in the RTW process after an acute cardiac event played by non-medical factors has been also explored by earlier research [3][4][5]9,[15][16][17][18][19][20][21][22][23]. Recent studies have shown that the perception of work environment, which can be reflected in work stress and job satisfaction, has a strong effect on both people's decision to RTW [16,21,22] and duration of sickness absence [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have found that predictors of HRQL after a heart surgery or coronary angioplasty were primarily psychological and not related to the illness severity [13][14][15][16]. Instead, research on professional life and work reintegration after cardiac interventions have focused mainly on the identification of factors predicting RTW (i.e., working/not working) or time for RTW [3,4,[17][18][19], while very few studies have investigated the quality of work resumption, in terms of a patient's job satisfaction and re-adaptation to work [15][16][17][18][19][20][21][22]. Recent studies suggested an important role of psychosocial work environment in the RTW process, with particular emphasis on work stress and job satisfaction [15,16,18,19,21,22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1) Comprehensive cardiac rehabilitation (CR) is an established program for patients with ACS after treatment by coronary artery bypass grafting (CABG) and heart failure 2) that helps to modify coronary risk factors and improve quality of life. 3,4) A metaanalysis has shown that CR reduces all-cause mortality by 20% and cardiac mortality by 25%. 5) The mechanisms through which CR improves mortality risk are attributed to improvements in lipid profiles, glucose metabolism, neurohormonal factors, autonomic nerve system, endothelial function, and reduced vascular inflammation.…”
mentioning
confidence: 99%